WHICH DINE OUTVARIABLESARE IMPORTANTINTHE RESTAURANTSELECTION PROCEDURE FOR BUSINESS PURPOSES: CASE STUDY OF UNIVERSITY COMMUNITY MEMBERS - CHANG LEE (Centre For Tourism Planning and Development, 2010)
The purpose of the study is to explore variables that university-associated members perceive to be important when they dine out for business purposes. The study explores whether importance of these variables are different according to demographic and dine out characteristics. Independent-sample t-test and Analysis of variance (ANOVA) are utilized for this study. The study indicates that variables that people consider more important compared to other factors are ones that directly related to peoples' dine out experiences. Items that are not directly related to actual dine out experience appear to be less important to university community members when they dine out.